Maxillary angiosarcoma: a case report and literature review - Kamdem Benedikta; Sala Nathalie; Broome Martin; May Laurence (Oral and Maxillofacial Surgery Cases)
Angiosarcoma is a rare and aggressive malignant mesenchymal neoplasia developing from endothelial cells, comprising only 2 % of soft tissues sarcomas. While primarily affecting soft tissues and skin, its occurrence in the oral cavity is exceptionally rare (1.6 %). We present the case of a 78-year-old woman with a nodular gingival lesion initially suspected as squamous cell carcinoma. Despite an uneventful postoperative course following maxillectomy, the histological examination revealed angiosarcoma. Discussion highlights the diagnostic challenges due to its varied clinical and histological presentation, often mimicking other lesions. Treatment involves complete surgical excision, followed by adjuvant chemotherapy and radiotherapy. However, the prognosis remains poor, with a high recurrence rate and metastatic potential. Our case underscores the importance of accurate diagnosis through comprehensive clinical, radiological, and histological evaluation, emphasizing the need for early detection and multidisciplinary management to improve outcomes in angiosarcoma patients.